The management of innovation in - Randall, Robyn Zoë (My University, 2011)
Innovation and therefore the management of innovation has increased in importance in recent times, as the need to grow, change and remain sustainable becomes a larger focus for organisations. In general, managers are more aware of their need to manage the process of innovation, but are still grappling with what they can do to improve innovation in their organisations. This study explores the understanding of innovation by managers in information-intensive organisations, as well as their approaches to innovation, in order to identify and assess the enablers of innovation within these types of organisations. In-depth, semi-structured interviews were used to obtain the views of middle to senior managers and executives at information-intensive organisations, on their innovation management approaches. The main finding of the research was that innovation is more than creativity and the thinking of ideas, but involves implementing those ideas, with a benefit to both organisation and customer. As a result, innovation needs to be consciously managed, through focusing on supporting the right behaviour and promoting the right culture. In addition, leadership has a critical role in communicating the innovation strategy, in order to provide context and direction for innovation within the organisation. Finally, support mechanisms for innovation are particularly important in allowing for the implementation of innovation and taking that innovation to market
MBA - WBS
Keywords: Innovation management; Innovation